Microbial Diversity and Biochemical Analysis of Suanzhou: A Traditional Chinese Fermented Cereal Gruel - Qin, Huibin; Sun, Qinghui; Pan, Xuewei; Qiao, Zhijun; Yang, Hongjiang (Frontiers in Microbiology, 2016)
Suanzhou as a traditional Chinese gruel is fermented from proso millet and millet. The biochemical analysis showed Suanzhou had relatively high concentrations of lactic acid, acetic acid, and free amino acids. The metagenomics of Suanzhou were studied, with the analysis of the V4 region of 16S rRNA gene, the genera Lactobacillus and Acetobacter were found dominant with the average abundance of 58.2% and 24.4%, respectively; and with the analysis of the ITS1 region between 18S and 5.8S rRNA genes, 97.3% of the fungal community was found belonging to the genus Pichia and 2.7% belonging to 5 other genera. Moreover, the isolates recovered from 59 Suanzhou samples with various media were identified with the 16S rRNA or 18S rRNA gene analyses. L. fermentum (26.9%), L. pentosus (19.4%), L. casei (17.9%), and L. brevis (16.4%) were the four dominant Lactobacillus species; A. lovaniensis (38.1%), A. syzygii (16.7%), A. okinawensis (16.7%), and A. indonesiensis (11.9%) were the four dominant Acetobacter species; and Pichia kudriavzevii (55.8%) and Galactomyces geotrichum (23.1%) were the two dominant fungal species. Additionally, L. pentosus p28-c and L. casei h28-c1 were selected for the fermentations mimicking the natural process. Collectively, our data demonstrate that Suanzhou is a nutritional food high in free amino acids and organic acids. Diverse Lactobacillus, Acetobacter, and yeast species are identified as the dominant microorganisms in Suanzhou. The isolated strains can be further characterized and used as starters for the industrial production of Suanzhou safely.